Downregulation of ATM Gene and Protein Expression in Canine Mammary Tumors - Raposo-Ferreira, T. M.M. [UNESP]; Bueno, R. C. [UNESP]; Terra, E. M. [UNESP]; Avante, M. L. [UNESP]; Tinucci-Costa, M. [UNESP]; Carvalho, M. [UNESP]; Cassali, G. D.; Linde, S. D. [UNESP]; Rogatto, S. R. [UNESP]; Laufer-Amorim, R. [UNESP] (SAGE Publications, 2016)
The ataxia telangiectasia mutated (ATM) gene encodes a protein associated with DNA damage repair and maintenance of genomic integrity. In women, ATM transcript and protein downregulation have been reported in sporadic breast carcinomas, and the absence of ATM protein expression has been associated with poor prognosis. The aim of this study was to evaluate ATM gene and protein expression in canine mammary tumors and their association with clinical outcome. ATM gene and protein expression was evaluated by reverse transcription-quantitative polymerase chain reaction and immunohistochemistry, respectively, in normal mammary gland samples (n = 10), benign mammary tumors (n = 11), nonmetastatic mammary carcinomas (n = 19), and metastatic mammary carcinomas (n = 11). Lower ATM transcript levels were detected in benign mammary tumors and carcinomas compared with normal mammary glands (P =.011). Similarly, lower ATM protein expression was observed in benign tumors (P =.0003), nonmetastatic mammary carcinomas (P <.0001), and the primary sites of metastatic carcinomas (P <.0001) compared with normal mammary glands. No significant differences in ATM gene or protein levels were detected among benign tumors and nonmetastatic and metastatic mammary carcinomas (P >.05). The levels of ATM gene or protein expression were not significantly associated with clinical and pathological features or with survival. Similar to human breast cancer, the data in this study suggest that ATM gene and protein downregulation is involved in canine mammary gland tumorigenesis.
Keywords: ataxia telangiectasia mutated (ATM); breast cancer; canine mammary tumor; comparative oncology; metastasis; protein expression